Firefighters’ occupational exposure to polycyclic aromatic hydrocarbons at Portuguese fire stations - Oliveira, M. (2017)
Polycyclic aromatic hydrocarbons (PAHs) are among the most relevant pollutants due to their toxic, mutagenic, and carcinogenic properties. Although scarce information exists regarding firefighters’ exposure to PAHs, there is a great gap of knowledge regarding this topic. Thus the aim of this study was to assess firefighters’ personal exposure to PAHs during regular work shifts at fire stations, with emphasis on carcinogenic compounds and potential heath risks.